2021
DOI: 10.3390/ijms22157890
|View full text |Cite
|
Sign up to set email alerts
|

Ozone in Medicine. The Low-Dose Ozone Concept and Its Basic Biochemical Mechanisms of Action in Chronic Inflammatory Diseases

Abstract: Low-dose ozone acts as a bioregulator in chronic inflammatory diseases, biochemically characterized by high oxidative stress and a blocked regulation. During systemic applications, “Ozone peroxides” are able to replace H2O2 in its specific function of regulation, restore redox signaling, and improve the antioxidant capacity. Two different mechanisms have to be understood. Firstly, there is the direct mechanism, used in topical treatments, mostly via radical reactions. In systemic treatments, the indirect, ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 24 publications
1
55
0
5
Order By: Relevance
“…Interestingly, most of the effects observed in non-activated fibroblasts are due to the exposure to 10 or 20 µg O 3 , i.e., the concentrations that have been already found as optimal for safely inducing positive response in various cell models [ 5 , 6 , 7 , 11 , 15 , 16 ]. This perfectly agrees with the low-dose concept in the medical use of O 3 [ 89 , 90 ], which is increasingly applied in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, most of the effects observed in non-activated fibroblasts are due to the exposure to 10 or 20 µg O 3 , i.e., the concentrations that have been already found as optimal for safely inducing positive response in various cell models [ 5 , 6 , 7 , 11 , 15 , 16 ]. This perfectly agrees with the low-dose concept in the medical use of O 3 [ 89 , 90 ], which is increasingly applied in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…Because the serum HDL is a macromolecular complex of phospholipid, cholesterol, and protein in serum [ 30 ], it can provide a good model to study the influence of ozonated oil on protein and lipid complexes. Recently, it was suggested that ozone peroxides are pharmacologically active substances that can replace H 2 O 2 to restore redox signaling and that can improve the antioxidant capacity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears clear that blood, in comparison to the corresponding plasma, is far less sensitive to ozone oxidation because of the presence of blood cells. The real mechanism of possible self-repair of the cells that have suffered the oxidative insult has not yet been defined, even if the hormesis theory of stress adaptation could represent the cellular response mechanisms to maintain homeostasis and cell survival [ 86 , 87 ].…”
Section: Molecular Aspectsmentioning
confidence: 99%